Understanding the Multiple Factor Determining of Z Generation to Hotel Staycation During Covid-19 Pandemic - Septi Fahmi Choirisa; Nosica Rizkalla (Sekolah Vokasi, Universitas Gadjah Mada, 2021)
The impact of the Covid-19 pandemic on restricted mobility, as well as a devastating economic development in various sectors, have change renewed interest in the future of tourism, especially in Hospitality Industry. This study sought to examine the Theory of Planned Behavior in the context of hotel staycation during the Covid-19 pandemic. Paired t-tests and the structural equation modelling were applied to assess the 246 responses of Z generations in Indonesia for the first and second quarters of 2021. The finding showed that attitude, perceived behavioral control, and subjective norms affect the hotel staycation intention during a pandemic for Z generations. Perceived behavioral control plays the most significant part. Several findings are provided on how the generation perceives traveling during the COVID-19 pandemic and how to encourage them to resume traveling after the travel restriction is lifted. Theoretical and practical implications are discussed. The viewpoint proffered in this study provides scopes of the hospitality industry in terms of hotel staycation programs to maintain a resilient economic strategy during the pandemic.